Lectotypification of three names in genus Delphinium (Ranunculaceae) from India - Agnihotri, Priyanka; Husain, Danish; Husain, Tariq (Phytotaxa, 2017)
In their monumental work Flora Indica, Hooker and Thomson (1855) described two new species under the genus Delphinium Linnaeus (1753: 530), namely D. viscosum Hooker f. & Thomson (1855: 52) and D. glaciale Hooker f. & Thomson (1855: 53) from the Sikkim Himalaya. In due course of revisionary studies in the genus Delphinium from India, the taxonomic difficulties associated with D. viscosum were addressed and resolved as a complex (Agnihotri et al., 2016). A thorough search of various national and international herbaria (BM, BSI, CAL, E, GH, JE, K, MEL, MH, NY and S: acronyms according to Thiers 2017 onwards) and a detailed study of both D. glaciale and D. viscosum complex have revealed that three names remain surrounded by uncertainty in typification. Therefore, a lectotype for the names D. glaciale, D. viscosum subsp. viscosum and D. viscosum subsp. gigantobracteum is selected here from amongst the original material.